THE IMAGE OF PROFESSIONAL FUTURE IN CRISIS STAGES OF TRAINING - Tatyana G. Bokhan; Lyudmila F. Alekseeva; Konstantin G. Yazykov; Marina V. Shabalovskaya; Svetlana A. Moreva (Высшее образование в России)
The article presents the results of the survey carried out by the chair of the general and differential psychology of the Siberian State Medical University. The aim of the survey was to reveal the substantial and dynamic aspects of an image of professional future of medical students and to define their psychological readiness for professional formation at «crisis» stages of education process. The analysis of the specific features of the meaning content of the professional future image shows its complication and transformation from junior to senior courses, which is the evidence of the dynamics of personal and professional formation of students.